Perfectionism as an expected job seekers’ social quality in online recruitment - Yu. A. Filyasova (Цифровая социология)
The aim of this paper is to define the meaning of perfectionism as a personal quality in online recruitment, from employers’ standpoint.   Job offers were searched on hh.ru with the help of the keyword ‘perfectionism’ and served as material for the research.   The main areas of professional activity appeared to be information technologies, marketing and management in thoseт areas.   The findings show that perfectionism is viewed by employers through the angle of professional motivation as a positive and wanted social quality in job seekers, which is placed in “Requirements” in the majority of job offers. Perfectionismт is viewed by employers as an idealistic image of a worker and is referred to three fields: professional activities, personality and communication. Analysis of associated personal qualitiesт gives evidence of immediate semantic perfectionist correlates: ambitiousness, professionalism, scrupulousness and analytical thinking. In a wider meaning, perfectionism is considered as a social and personal characteristic of an employee, both efficient and initiative, wearing a dress code specified by internal corporate rules, open-minded, internally motivated and capable of fulfilling duties within the established deadline, ready to suggest effective approaches to organizing business processes and to work overtime, completing extensive assignments, to work more than is mentioned in work duties; perfectionism characterizes a loyal employee willing to participate at full capacity in developing the organization, to efficiently interact with internal and external communicants and to actively contribute to organization performance and competitiveness.